2013
DOI: 10.1021/es304135b
|View full text |Cite
|
Sign up to set email alerts
|

A GIS Cost Model to Assess the Availability of Freshwater, Seawater, and Saline Groundwater for Algal Biofuel Production in the United States

Abstract: A key advantage of using microalgae for biofuel production is the ability of some algal strains to thrive in waters unsuitable for conventional crop irrigation such as saline groundwater or seawater. Nonetheless, the availability of sustainable water supplies will provide significant challenges for scale-up and development of algal biofuels. We conduct a partial techno-economic assessment based on the availability of freshwater, saline groundwater, and seawater for use in open pond algae cultivation systems. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
98
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 16 publications
0
98
2
1
Order By: Relevance
“…Culture temperature and algae productivity was evaluated integrating a reactor thermal model with an algae growth and lipid accumulation model. Venteris et al [38], Venteris et al [42], Venteris et al [39], and Wigmosta et al [34] used stochastically generated 30-year daily weather data for 2600 US locations (Cligen weather generator [58]). The daily weather data was disaggregated to hourly values of temperature, precipitation, solar radiation, dew-point, pan evaporation, and wind speed.…”
Section: Climatementioning
confidence: 99%
“…Culture temperature and algae productivity was evaluated integrating a reactor thermal model with an algae growth and lipid accumulation model. Venteris et al [38], Venteris et al [42], Venteris et al [39], and Wigmosta et al [34] used stochastically generated 30-year daily weather data for 2600 US locations (Cligen weather generator [58]). The daily weather data was disaggregated to hourly values of temperature, precipitation, solar radiation, dew-point, pan evaporation, and wind speed.…”
Section: Climatementioning
confidence: 99%
“…One study has evaluated the available water sources in the US in order to evaluate the land available for microalgae cultivation, and to assess how well the availability would meet with the demand for fuel. They conclude that within the US, despite higher productivities than other biocrops, land availability still challenges the ability to provide enough fuel from microalgae as a sole feedstock [72,75].…”
Section: Land Use Change (Direct and Indirect)mentioning
confidence: 99%
“…Independent analysis has shown that the gulf coast might be the best place to grow algae from a water perspective and this region could be the most desirable in terms of CO 2 availability as well (131). As shown in Figure 5.6, Louisiana has a number of large and currently untapped CO 2 resources that are tied to the significant refining capacity of the Louisiana.…”
Section: Resultsmentioning
confidence: 99%